Safety assessment of cyclin-dependent kinase 4/6 inhibitors and comparison of time to adverse events - Siqi Zhang; Renmin Zhang; Yingzi Xia; Dingwen Cao (PLoS ONE, 2025)
Background Multiple CDK4/6 inhibitors have been approved for the treatment of HR + /HER2- advanced breast cancer. Nevertheless, there is currently a scarcity of safety reports on CDK4/6 inhibitors within large sample cohorts. Methods We employed a disproportionality analysis of the FAERS database to detect safety signals for the three marketed CDK4/6 inhibitors (palbociclib, abemaciclib, and ribociclib). We retrieved pertinent reports from 2004 Q1 to 2023 Q3. Four asymmetric analyses were utilized to assess signals. Results A total of 459 positive signals were obtained at the preferred term level (146 positive signals for palbociclib, 68 positive signals for abemaciclib, 245 positive signals for ribociclib). Palbociclib-related adverse events were commonly fatigue, white blood cell count decreased, alopecia. Abemaciclib-related adverse events were commonly diarrhea, decreased appetite, dehydration. Ribociclib-related adverse events were commonly neutropenia, white blood cell count decreased and decreased immune responsiveness. Unexpected adverse events related to palbociclib included hot flush, bone marrow failure. Unexpected adverse events related to abemaciclib included myelosuppression, dehydration, and cystatin C increased. Unexpected adverse events related to ribociclib included decreased immune responsiveness, pleural effusion, atrioventricular conduction time shortened. Conclusion Our research corroborates the typical adverse events linked to CDK4/6 inhibitors while highlighting potential safety concerns in their real-world clinical application.